Society’s Attitude Toward Spousal Physical Abuse: Findings from the Philippines National Demographic and Health Survey, 2022 - Wah Wah Myint; Roaa Aggad; Qiping Fan; Chimuanya Osuji; Heather R. Clark; E. Lisako Jones McKyer (Women's Health Reports)
Background: Societal attitude toward spousal physical abuse plays a crucial role in preventing violence against women. Yet, this public health issue has been insufficiently addressed. This study examines the relationship between the societal attitude toward spousal physical abuse and various social determinants. Methods: We used data from the 2022 Philippines’ National Demographic and Health Survey. The outcome variable was attitude toward spousal physical abuse. Covariates included women’s sociodemographic characteristics, experiences of witnessing their father’s abusive behavior, intimate partner violence (IPV), and controlling behavior. Partner-related variables (age, educational level, employment status, and alcohol consumption behavior) were also considered. Descriptive and logistic regression analyses were performed to examine the associated factors of spousal physical abuse by using Stata 18.0. Results: Overall, 1,920 (9%) of 19,228 women reported that spousal physical abuse is justifiable in at least one of the presented scenarios. Women IPV survivors (adjusted Odds Ratio [aOR] = 1.35, 95% confidence interval [95% CI] = 1.06–1.73) and those who experienced controlling behavior by their partners (aOR = 1.77, 95% CI = 1.45–2.15) were more likely to accept spousal physical abuse than their counterparts. Conversely, women with a higher decision-making score were less likely to accept spousal physical abuse than those who had a lower score (aOR = 0.74, 95% CI = 0.56–0.98). Conclusions: Finding suggests that women’s attitudes toward spousal physical abuse are significantly influenced by their experience of IPV. Future health research, programs, and policies should address individual, interpersonal, and systemic-level risk factors that profoundly impact women’s health.